Case Report: Effective methotrexate removal by combined hemodialysis and polymeric resin hemoadsorption - Dias, Maria Rita; Nicolau, Carla; Ferreira, Hugo; Chacim, Sérgio; Oliveira, Isabel; de Câmara Negalha, Gonçalo; Mariz, José Mário; Costa, José Maximino (Frontiers in Nephrology, 2025)
BackgroundHigh-dose methotrexate (HDMTX) is central to treating primary central nervous system lymphoma but carries a risk of acute kidney injury (AKI), which can delay methotrexate (MTX) clearance and increase toxicity. Glucarpidase is the treatment of choice for MTX toxicity, but limited access in many countries may necessitate alternatives. We present the first reported adult case of combined high-flux hemodialysis (HFHD) and HA230 hemoadsorption for MTX clearance.Case summaryA 66-year-old woman with newly diagnosed primary central nervous system lymphoma began induction chemotherapy including HDMTX. Forty-eight hours post-infusion, she developed KDIGO stage 3 AKI, with plasma MTX levels of 26.278 µmol/L despite maintained urine output and early supportive measures. On Day 3, MTX levels remained elevated at 15.567 µmol/L, accompanied by severe metabolic alkalosis. She was admitted to intensive care, where she underwent HFHD combined with post-filter HA230 hemoadsorption, followed by intravenous glucarpidase as soon as it became available. A second extracorporeal session occurred 48 hours later. MTX levels decreased by 91.93% (estimated elimination half-life ≈ 0.83 hours) and 71.02% (half-life ≈ 2.12 hours) after the first and second sessions, respectively. No significant rebound in MTX levels or dialysis-related complications occurred. The patient recovered renal function and completed further treatment without MTX.ConclusionsThis case demonstrates the effectiveness of combined HFHD and HA230 hemoadsorption as a bridging or alternative strategy when glucarpidase is delayed or unavailable. While evidence remains limited, it supports further investigation into extracorporeal MTX removal and contributes to the evolving field of Onconephrology.